Sex-Specific Skeletal Muscle Fatigability and Decreased Mitochondrial Oxidative Capacity in Adult Rats Exposed to Postnatal Hyperoxia - Tetri, Laura H.; Diffee, Gary M.; Barton, Gregory P.; Braun, Rudolf K.; Yoder, Hannah E.; Haraldsdottir, Kristin; Eldridge, Marlowe W.; Goss, Kara N. (Frontiers in Physiology, 2018)
Premature birth affects more than 10% of live births, and is characterized by relative hyperoxia exposure in an immature host. Long-term consequences of preterm birth include decreased aerobic capacity, decreased muscular strength and endurance, and increased prevalence of metabolic diseases such as type 2 diabetes mellitus. Postnatal hyperoxia exposure in rodents is a well-established model of chronic lung disease of prematurity, and also recapitulates the pulmonary vascular, cardiovascular, and renal phenotype of premature birth. The objective of this study was to evaluate whether postnatal hyperoxia exposure in rats could recapitulate the skeletal and metabolic phenotype of premature birth, and to characterize the subcellular metabolic changes associated with postnatal hyperoxia exposure, with a secondary aim to evaluate sex differences in this model. Compared to control rats, male rats exposed to 14 days of postnatal hyperoxia then aged to one year demonstrated higher skeletal muscle fatigability, lower muscle mitochondrial oxidative capacity, more mitochondrial damage, and higher glycolytic enzyme expression. These differences were not present in female rats with the same postnatal hyperoxia exposure. This study demonstrates detrimental mitochondrial and muscular outcomes in the adult male rat exposed to postnatal hyperoxia. Given that young adults born premature also demonstrate skeletal muscle dysfunction, future studies are merited to determine whether this dysfunction as well as reduced aerobic capacity is due to reduced mitochondrial oxidative capacity and metabolic dysfunction.